The Comparison of the Use of Data-driven Learning in Flipped,, Blended and Conventional Classes on Students’ Grammar Learning - Hooshang Khoshsima (Journal of English Language Teaching and Learning, 2021)
Today, the use of technology in teaching foreign language has become a matter of considerable interest to language teachers in all over the world. The current study tried to investigate the suitability of data-driven learning in flipped and blended classes vs the conventional ones on students’ grammar learning. To run this study, 48 homogenized students were selected and divided into three groups, including two experimental and one control group, 16 in each. Before the treatment, a grammar pre-test was administered. The two experimental groups received 12 sessions of data-driven instruction in the flipped and blended classes but the control group received grammar instruction based on the textbook. At the end, statistical analysis showed that the participants in both flipped and blended groups had better performance in the post-test. It also was concluded that the usage of data-driven learning had significant impact on both experimental groups. The results of this study can be beneficial for teachers, learners, syllabus designers, managers in learning environments, and policy makers to use data driven learning.